A Thematic Linguistic Analysis of TESOL Students' Commitment to Intercultural Communication Values. Issue 4 (26th December 2019) - Cutting, Joan
Abstract : This article describes a study of TESOL preservice teacher journals that used a thematic linguistic framework of analysis aimed at revealing the extent of their commitment to intercultural communication values, as evidenced by their attitude to cultural differences and stereotyping, and their stance markers. Nearly all entries showed the students' ability to decenter, question the values of their own culture, and accept the values of the other culture. A minority of students took a nonessentialist view of culture and preferred to look at the influence of social variables such as age on language. On the other hand, a third of all entries contained polarization of overgeneralized cultural differences, juxtaposed negative words, critical intensifiers, negative hyperboles, and triple repetitions of critical hyperboles, all unconvincingly softened by expressions of weak epistemic stance. The article ends with a suggestion of how teacher educators can carry out a similar study of their preservice teachers' discourse to understand their beliefs and help them become aware of how their attitudes can be revealed by destructive culturalist language.